Gender difference effects on contributing factors of intention to be involved in knowledge creation and sharing - Mohamed Jalaldeen , Mohamed Razi; Nor Shahriza, Abdul Karim; Norshidah, Mohamed (Asian Economic and Social Society (AESS), 2014)

(untitled)
The paper analyses the moderating effects of demographics factors of organizational members on the contributing factors of intention to be involved in Knowledge Management (KM) process; knowledge creation and knowledge sharing. The KM processes were operationalized through knowledge creation theory (SECI process). Data were collected from 313 executives in the Sri Lankan Telecommunication Industry using self-administered questionnaires. Two KM enablers; ‘trust & collaboration’ and ‘ICT use and support for search and sharing’, and two individual acceptance factors; ‘performance expectancy of KM’, and ‘effort expectancy of KM’ were considered as contributing factors of intention to be involved in KM process. The study found that gender moderates the relationship between ‘ICT use and support for search and sharing’, ‘performance expectancy of KM’ and intention to be involved in KM process. The findings suggest that if the policy makers in the industry are planning to implement KM initiatives, they should consider gender differences of the executives and the strategies should be formulated accordingly